Efektivitas Metode Peer Teaching terhadap Hasil Belajar Matematika - Ita Ita; Azwar Anwar; Alfian Mucti (Pendidikan Matematika FKIP Universitas Mataram, 2022)
This research was conducted to see whether the Peer Teaching method was effective in learning mathematics in class IX at SMP Negeri 4 Tarakan. This study uses a posttest-only control design with a quasi research type. The research was conducted at Tarakan 4 Public Middle School and the research population was class IX for the 2022/2023 academic year. The sampling method is Simple Random Sampling, with class IX-8 as the control class and class IX-10 as the experimental class. Data collection with description test instruments and documentation. The analysis technique uses descriptive analysis and inferential analysis. Descriptive analysis namely standard deviation and average. Then test the hypothesis using the independent sample t-test (t test). The research results obtained 4.140 > 1.672, so H0 was rejected, namely the peer teaching method was effective for class IX student learning outcomes at SMP Negeri 4 Tarakan. Keywords: Mathematics Learning Outcomes, Peer Teaching